Assembling two Dy2 single-molecule magnets with different energy barriers via fine-tuning the geometries of DyIII sites. (20th November 2020) - Li, Dawei; Ding, Man-Man; Ge, Yu; Tello Yepes, David Felipe; Sun, Mingyuan; Najib, Muhammad Saleem; Li, Yahong; Zhang, Yi-Quan; Yao, Jin-lei
Abstract : Two Dy2 single-molecule magnets are prepared. The energy barrier of 2 is slightly enhanced by adjusting the geometries of Dy III centers. Abstract : The utilization of two Schiff-base ligands H2 L 1 and H2 L 2 (H2 L 1 = 4-chloro-2-(((3-ethoxy-2-hydroxybenzyl)imino)methyl) phenol, H2 L 2 = 2-(((3-ethoxy-2-hydroxybenzyl)imino)methyl)-4-methoxy-phenol) with different substituents at the backbone of phenol in the construction of dinuclear dysprosium single-molecule magnets (SMMs) is reported. Two complexes of formulae [Dy2 (L 1 )2 (NO3 )2 (EtOH)(DMF)]·2EtOH (1 ) and [Dy2 (L 2 )2 (NO3 )2 (MeOH)2 ] (2 ) have been prepared and structurally characterized. X-ray crystallographic analysis revealed that the four Dy III ions of 1 and 2 all adopt NO7 coordination environments. The two Dy III centers of 1 exhibit triangular dodecahedron ( D 2d ) and square antiprism ( D 4d ) geometries, respectively, while the two Dy III sites in 2 both show triangular dodecahedron geometry with D 2d symmetry. Magnetic analyses indicated that both complexes display SMM behavior with energy barriers of 86.91 K (1 ) and 93.70 K (2 ), respectively. The slight enhancement of the energy barrier of 2 reveals that the coordination geometries of Dy III ions would affect the magnetic behaviors of 1 and 2 . Complete Active Space Self-Consistent Field (CASSCF) calculations were conducted for 1 and 2 to illustrate the slight variation of the magnetic behaviors. The calculated results are well consistent with those of the experimental outcomes.